Using Environmental Marketing Tools in the Implementation of the Concept of Sustainable Development of the Region - Bolotina, Y.; Shubna, O.; Nykolaiva, Y. (Економічний вісник Донбасу, 2019)
The article describes the development of the concept of ecological marketing in the region. It has been determined that in the existing ecological, social and economic conditions, the main tasks of ecological marketing in the region include the tasks of forming and developing the environmental goods market in order to resolve differences between economic development and the need to preserve and further improve environmental quality. A mechanism for calculating the price of environmental goods. It is determined that the main elements of communications in the system of environmental marketing is advertising, sales promotion, public relations and personal selling. Communication activities help build trust with producers and their products, help explain the content and meaning of ecolabeling, which is an advertising medium and can serve as a guide for consumers when choosing products and increasing the competitiveness of products.